2009
DOI: 10.1029/2008jd011288
|View full text |Cite
|
Sign up to set email alerts
|

Is summer monsoon rainfall decreasing over India in the global warming era?

Abstract: [1] Using long-term (1871-2005) summer monsoon rainfall data over 30 meteorological subdivisions of India, overall tendencies of the rainfall have been studied. Further, the subseasonal (monthly) trends have been evaluated. For this purpose, simple linear regression technique is applied. To examine the trends in different segments for summer monsoon rainfall, 11-year running averages are calculated. Most of the subdivisions reveal systematic increasing and decreasing trends in different segments of the time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 26 publications
2
76
0
Order By: Relevance
“…Thus, the westward shift of large-scale circulation over the Indo-Pacific sector seems to modulate the convective activities over the India-Pakistan monsoon trough region. It may be also noted that various recent studies (Goswami et al, 2006;Guhathakurta and Rajeevan, 2008;Naidu et al, 2009) have investigated the trend in Indian summer monsoon rainfall over a longer period (more than a century) and concluded that the various regions of India (e.g. Central India, west coast, northeast sector) depict a gradual increasing/decreasing trend.…”
Section: Extended Analysis Over 1948-2010mentioning
confidence: 99%
“…Thus, the westward shift of large-scale circulation over the Indo-Pacific sector seems to modulate the convective activities over the India-Pakistan monsoon trough region. It may be also noted that various recent studies (Goswami et al, 2006;Guhathakurta and Rajeevan, 2008;Naidu et al, 2009) have investigated the trend in Indian summer monsoon rainfall over a longer period (more than a century) and concluded that the various regions of India (e.g. Central India, west coast, northeast sector) depict a gradual increasing/decreasing trend.…”
Section: Extended Analysis Over 1948-2010mentioning
confidence: 99%
“…This trend mainly results from decreasing summer precipitation rates after the 1960s, and is associated with a weakening of the Southern Oscillation and a decrease in temperature gradients over southern Asia due to high warming rates over the Indian Ocean during recent decades (Basistha et al, 2009;Naidu et al, 2009). Long-term trends of winter precipitation rates are slightly negative but not statistically significant (Bhutiyani et al, 2010).…”
Section: Regional Climate Changementioning
confidence: 99%
“…Mainly natural processes and persistent anthropogenic influences are responsible for it, altering the composition of the global atmosphere and natural climatic system. According to Intergovernmental Panel on Climate Change Fourth Assessment Report the world indeed has become more drought prone with higher frequencies of extreme events (IPCC REPORT, 2007) some clear instances around the world can be noticed ,like changing trends of monsoonal rainfall over India due to climate change (Naidu et al, 2009) increase in drought events in UK (Arnell, 2007), in Korean peninsula (Kyoung et al, 2011), in Iran (Sayari et al, 2013), and over Indian subcontinent (Sivakumar and Stefanski, 2011) describing the impacts of climate change. In India, 80% of annual rainfall comes from southwest monsoon, and very important for the whole country, especially for the low rainfall belts like Rajasthan state.…”
Section: Introductionmentioning
confidence: 99%